VD_FINDINFO Jug / 2017 / 112 vom 17. November 2016 - VD Tribunal cantonal (2016)
IN DUBIO PRO REO, APPAREIL DE PRISE DE VUE, APPRÉCIATION DES PREUVES | 179sexties CP, 10 al. 1 CPP (CH), 10 al. 2 CPP (CH)